Spontaneous Chylothorax following Septic Pulmonary Embolization - Michael Agustin; Michele Yamamoto; Chawat Tongma; Leslie Anne Chua; Michael Torres; Scott Shay (Case Reports in Pulmonology)
Chylothorax is the occurrence of chyle (lymph) in the pleural cavity secondary to damage of the thoracic duct. It is a rare form of pleural effusion which appears as a milky white turbid fluid. Malignancy is the leading cause of nontraumatic chylothorax while inadvertent surgical injury to the thoracic duct is the major cause of traumatic chylothorax. We report a case of spontaneous left-side chylothorax following septic pulmonary embolization (SPE) with Methicillin-Resistant Staphylococcus aureus (MRSA). This is a rare case of a nonmalignant, nontraumatic, and nontuberculous spontaneous chylothorax which was conservatively treated with fibrinolysis and diet modification.